2016
DOI: 10.1051/mfreview/2016008
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into initiation and propagation of cracks in the coated surfaces of spur gears with submodelling and irreversible cohesive-zone modelling techniques

Abstract: -Spur gears are one of the commonly used transmission parts in industry, due to its simplicity in structures and low cost in manufacturing. Due to a performance requirement, a spur gear may be coated with a specific coating arrangement. Under working conditions, the coating on the teeth may be damaged due to contact fatigue, in the forms such as micro-pitting and/or delamination. The failure mechanism of the coated surface under the gearing contact loading has been investigated intensively through experiment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…The previous studies demonstrated that the cohesive zone model can predict load bearing capacity of coated systems under the monatomic loading through tracking the initiation and propagation of cracks within the coating [14,20,21,27]. In this study, the irreversible cohesive zone model, allowing for the crack initiation and propagation to be tracked under cyclic loading, has been used to predict the loading bearing capacity under the fatigue loading condition.…”
Section: Prediction Of the Load Bearing Capacity Under The Contact Fa...mentioning
confidence: 99%
See 1 more Smart Citation
“…The previous studies demonstrated that the cohesive zone model can predict load bearing capacity of coated systems under the monatomic loading through tracking the initiation and propagation of cracks within the coating [14,20,21,27]. In this study, the irreversible cohesive zone model, allowing for the crack initiation and propagation to be tracked under cyclic loading, has been used to predict the loading bearing capacity under the fatigue loading condition.…”
Section: Prediction Of the Load Bearing Capacity Under The Contact Fa...mentioning
confidence: 99%
“…Numerical analysis of fatigue behaviour of both steel and light alloy when coated with thin hard coating has been little studied so far due to (i) the limitation of the computation capability in term of the temporal evolution and mesh size, (ii) challenges of the complicated contact boundary conditions and (iii) evolution of the material properties with history of loading. To date, only a few studies have investigated fatigue damage for coated gears [13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, FE simulation has become an increasing important tool for investigating metal forming processes [18][19][20]. FE simulation can provide convenience not only to make clear the forming mechanisms, temperature effects, traces of deformation, microstructure evolutions and an insight into how defects arise during the forming process, but also to give an efficient method to identify and optimize important process parameters without expensive experiments [21][22][23][24]. Therefore, it's important to develop a reasonable FE model for the investigation and understanding of tube warm-bending, which should be as consistent with the real conditions as possible and can save computation time.…”
Section: Introductionmentioning
confidence: 99%